Teachers' Language Use in Multilingual Head Start Classrooms: Implications for Dual Language Learners - Megan Chan; Maria Belen Buttiler; Francis Yang; Jerry Yang; Yuuko Uchikoshi; Qing Zhou (MDPI AG, 2022)
Dual language learners (DLLs) are sensitive to teachers' language influence in early childhood classrooms. In this mixed methods study incorporating 53 teachers from 28 preschools in Northern California, we investigated the characteristics of teachers' language use in preschools teaching Chinese-English and Spanish-English DLLs. We further examined the links of teachers' language use to the DLLs' expressive vocabulary in English and their heritage language (HL), controlling for home language exposure and other confounding variables. Finally, we conducted interviews with teachers to understand how they make meaning of their daily language practices. The sample of children consisted of 190 Chinese-English (N = 125) and Spanish-English (N = 65) DLLs (mean age = 48.3 months; 48% females). The teacher survey showed that most teachers spoke two or more languages and used a mix of English and their HL during their interactions with DLLs. The results of random-intercept models showed that teachers' language use did not uniquely predict children's vocabulary, controlling for family-level factors. However, the teachers with more years of teaching DLLs oversaw children with a higher HL vocabulary. The interview data revealed that teachers employ several strategies to communicate with DLLs and support HL maintenance. Our study reveals the multilingual backgrounds of preschool teachers and the rich language strategies they implement in multilingual classrooms. Future directions concerning the quality and development of teachers' language use are discussed.